2018
DOI: 10.1002/etc.4041
|View full text |Cite
|
Sign up to set email alerts
|

Copper uptake, patterns of bioaccumulation, and effects in glochidia (larvae) of the freshwater mussel (Lampsilis cardium)

Abstract: The early life stages of freshwater mussels are particularly sensitive to copper (Cu) contamination. We measured the acute toxicity, bioaccumulation, and sublethal effects of Cu in glochidia. In addition, we used radiolabeled Cu ( Cu) to examine the time-dependent kinetics of uptake over 24 h. Uptake of Cu by live and dead glochidia exposed to 0.11 μmol/L exhibited similar hyperbolic patterns over the first 40 min, indicating an adsorptive phase independent of larval metabolism. Thereafter, uptake was linear w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…One explanation for these findings may be related to mussels hosting antibiotic resistant symbionts ( Cooke, 1976 ; Liu et al, 2016 ), multidrug-resistant pathogens, ( da Silveira et al, 2016 ), and enhanced horizontal gene transfer within their gut microbial community ( Grevskott et al, 2017 ). Previous research has also shown that mussels bioaccumulate various metals ( Naimo, 1995 ; Rzymski et al, 2014 ), including elements found in this genetic marker study, copper and zinc ( Jorge et al, 2018 ). It is possible that horizontal gene transfer of multidrug resistance was facilitated by symbionts in mussel biodeposits, or from the decay of mussel tissue after death.…”
Section: Discussionsupporting
confidence: 65%
“…One explanation for these findings may be related to mussels hosting antibiotic resistant symbionts ( Cooke, 1976 ; Liu et al, 2016 ), multidrug-resistant pathogens, ( da Silveira et al, 2016 ), and enhanced horizontal gene transfer within their gut microbial community ( Grevskott et al, 2017 ). Previous research has also shown that mussels bioaccumulate various metals ( Naimo, 1995 ; Rzymski et al, 2014 ), including elements found in this genetic marker study, copper and zinc ( Jorge et al, 2018 ). It is possible that horizontal gene transfer of multidrug resistance was facilitated by symbionts in mussel biodeposits, or from the decay of mussel tissue after death.…”
Section: Discussionsupporting
confidence: 65%
“…This process may eventually lead to formation of LPO and impairment of membrane function (Halliwell and Gutteridge, 2006). Exposure of M. galloprovincialis to Cu alone did not result in LPO level increase although a strong pro-oxidant activity of Cu was previously reported for bivalves (Jorge et al, 2018;Katsumiti et al, 2018).…”
Section: Discussionmentioning
confidence: 83%
“…Among aquatic organisms, freshwater mussels are highly sensitive to acute Cu exposure (Wang et al, 2011;Giacomin et al, 2013), while bivalve mussels have been widely deployed in ecotoxicology studies (Caricato et al, 2019). Chronic exposure to Cu at sublethal concentrations might lead to both ionoregulatory disturbance and oxidative stress in freshwater bivalves (Jorge et al, 2013(Jorge et al, , 2018. The activity of the osmoregulatory enzymes Na + /K + -ATPase (NKA) has been investigated as a potential target of Cu effects (Jorge et al, 2013(Jorge et al, , 2018Fan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic exposure to Cu at sublethal concentrations might lead to both ionoregulatory disturbance and oxidative stress in freshwater bivalves (Jorge et al, 2013(Jorge et al, , 2018. The activity of the osmoregulatory enzymes Na + /K + -ATPase (NKA) has been investigated as a potential target of Cu effects (Jorge et al, 2013(Jorge et al, , 2018Fan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%